Accuracy of electrocardiography in diagnosis of left ventricular hypertrophy in arterial hypertension: systematic review. Issue 7622 (28th August 2007) - Pewsner, Daniel; Jüni, Peter; Egger, Matthias; Battaglia, Markus; Sundström, Johan; Bachmann, Lucas M
Abstract : Objective To review the accuracy of electrocardiography in screening for left ventricular hypertrophy in patients with hypertension. Design Systematic review of studies of test accuracy of six electrocardiographic indexes: the Sokolow-Lyon index, Cornell voltage index, Cornell product index, Gubner index, and Romhilt-Estes scores with thresholds for a positive test of ≥4 points or ≥5 points. Data sources Electronic databases ((Pre-)Medline, Embase), reference lists of relevant studies and previous reviews, and experts. Study selection Two reviewers scrutinised abstracts and examined potentially eligible studies. Studies comparing the electrocardiographic index with echocardiography in hypertensive patients and reporting sufficient data were included. Data extraction Data on study populations, echocardiographic criteria, and methodological quality of studies were extracted. Data synthesis Negative likelihood ratios, which indicate to what extent the posterior odds of left ventricular hypertrophy is reduced by a negative test, were calculated. Results 21 studies and data on 5608 patients were analysed. The median prevalence of left ventricular hypertrophy was 33% (interquartile range 23-41%) in primary care settings (10 studies) and 65% (37-81%) in secondary care settings (11 studies). The median negative likelihood ratio was similar across electrocardiographic indexes, ranging from 0.85 (range 0.34-1.03) for the Romhilt-Estes score (with threshold ≥4 points) to 0.91 (0.70-1.01) for the Gubner index. Using the Romhilt-Estes score in primary care, a negative electrocardiogram result would reduce the typical pre-test probability from 33% to 31%. In secondary care the typical pre-test probability of 65% would be reduced to 63%. Conclusion Electrocardiographic criteria should not be used to rule out left ventricular hypertrophy in patients with hypertension.